Naming violence: a critical theory of genocide, torture, and terrorism - Thaler, Mathias (New directions in critical theory, 2018)
Much is at stake when we choose a word for a form of violence: whether a conflict is labeled civil war or genocide, whether we refer to “enhanced interrogation techniques” or to “torture,” whether a person is called a “terrorist” or a “patriot.” Do these decisions reflect the rigorous application of commonly accepted criteria, or are they determined by power structures and partisanship? How is the language we use for violence entangled with the fight against it? In Naming Violence, Mathias Thaler articulates a novel perspective on the study of violence that demonstrates why the imagination matters for political theory. His analysis of the politics of naming charts a middle ground between moralism and realism, arguing that political theory ought to question whether our existing vocabulary enables us to properly identify, understand, and respond to violence. He explores how narrative art, thought experiments, and historical events can challenge and enlarge our existing ways of thinking about violence. Through storytelling, hypothetical situations, and genealogies, the imagination can help us see when definitions of violence need to be revisited by shedding new light on prevalent norms and uncovering the contingent history of ostensibly self-evident beliefs. Naming Violence demonstrates the importance of political theory to debates about violence across a number of different disciplines from film studies to history.